Rent2U – Mobile application for rental equipment at UiTM Shah Alam / Muhammad Firdaus Suhaimi - Suhaimi, Muhammad Firdaus (2021)
This project is about the development of a mobile application for rental equipment at UiTM Shah Alam. The reason for the development of this project is to help the students of UiTM Shah Alam to rent items and equipment that they need. A mobile application for rental equipment can solve problems such as most students are not able to afford new items and belongings. On some occasions, students also need specific items to attend a one-time event without overspending and they are unable to explore new hobbies without spending too much. Therefore, this project aims to develop an Android-based mobile application called Rent2U that can help students of UiTM Shah Alam to rent items and equipment that they need. The objectives of this project were to identify the requirements, to design, and to develop equipment rental application at UiTM Shah Alam. The chosen methodology for the development of this mobile application is the Mobile Application Development Lifecycle (MADLC). However, this project covered up until the testing phase only. Apart from that, the features of this mobile application include geolocation to find nearby items and equipment for rentals, search function to find items and equipment, and push notifications to alert the users about the listings that have been created by them for rental. The limitation of this project is that the mobile application cannot integrate with the payment gateway and the use of it is not be available in the mobile application. Hence, the significance of this project is that it can help the students and staff to rent and lend items and equipment by providing the users a platform for them to lend their belongings and at the same time able to rent items and equipment that they like. For future enhancements, this application may include a variety of options for the users to pay such as online banking, credit card, and others. Other than that, the application may also include goods and equipment verification to avoid dangerous items from being rented.